The Idea and Ideal of the Town between Late Antiquity and the Early Middle Ages
1 online resource.
Keywords: This volume examines the changing perceptions and ideals of town life, from the classical civitas/polis (the lynch-pin of ancient civilisation) to the medieval city (still playing many central roles, but with less of the ideological charge characteristic of Antiquity). One central theme is the persistent 'shadow' of the ancient city - in crumbling ancient buildings, and the survival of Roman styles of urban lay-out; and in the way that cities were depicted both visually (in persistence of often outmoded classical terms and descriptions), and verbally (in the persistence of often outmoded classical terms and descriptions). Yet the ideal of the city was also changing and developing, especially around the idea of a new, specifically Christian city, protected by its saints and by its churches.